7y-63=2y

Simple and best practice solution for 7y-63=2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-63=2y equation:



7y-63=2y
We move all terms to the left:
7y-63-(2y)=0
We add all the numbers together, and all the variables
5y-63=0
We move all terms containing y to the left, all other terms to the right
5y=63
y=63/5
y=12+3/5

See similar equations:

| -6-2(4x-1)+5x=14 | | -2d=30 | | 5+9z=9z | | -7=b/17 | | 4x-2=0.5x | | 1/6d+2/3=1/4-0.5 | | 15p+p=7=12p | | 0.5x+2x+45=150 | | 4(3x−2)+5=5−3(2x+1) | | .-6(3-7n)=-345 | | 2(z-21)+4(1-3)=60 | | (3x)=0.5(4x+20) | | 5x15=465 | | 275=-9(4+5v)-4 | | 8=2x=5(x-4) | | -31-4=-5-5-5(1+5x | | 4.5z=4.5z-6.5+6.25 | | 4x-5=3×+2 | | 1850=6x+650 | | (2x)=0.5(10x+-21) | | -20+2(11-2x)=26 | | 14x+3+4x+5=54 | | –5j−8=4−9j | | 3(x+2)+4(x+2)=28 | | -7+x/4=-3 | | 16=k+18 | | 2n+10=10+2n | | 3774x−37=74x−37 | | 6(x-3)=2x+4 | | 7p=–7+7p | | 4xx9=72 | | 1-a-6a=1 |

Equations solver categories